Retinal thickness in diabetic and non-diabetic patients using spectral domain optical coherence tomography (SD-OCT) - Memon, Muhammad Asif; Jatoi, Mehak Nazir; jamali, Anam; Pirzada, Saba (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
This study aimed to determine the average retinal thickness with and without diabetes using Spectral Domain Optical Coherence Tomography (SD-OCT). Known diabetic and non-diabetic respondents from Diabetic Eye Clinic & General OPD having no clinical signs of diabetic retinopathy on fundus examination were selected in this study. All the participants gave informed written informed consent. A total of 80 patients (n=156 eyes) were recruited in this study. Average central thickness was 249 µm and 246 µm in diabetic and non-diabetic patients respectively. On quadrant wise evaluation, retinal thickness in diabetic and non-diabetic (Healthy Eye) were: Nasal =310 µm and 324 µm), Temporal =291 µm and 304 µm, Superior =297 µm and 316µm, and Inferior= 292 µm and 314 µm). Retinal thicknesses were greater at nasal and lesser at temporal areas. In conclusion retinal thickness measured in diabetic patients was found to be less in non-diabetic patients. Age and gender were other related demographic factors that influenced macular thickness measurements.